Enhanced physical therapy improves recovery of arm function after stroke. A randomised controlled trial. Issue 7 (July 1992) - Sunderland, A; Tinson, D J; Bradley, E L; Fletcher, D; Langton Hewer, R; Wade, D T
Abstract : Previous research on stroke rehabilitation has not established whether increase in physical therapy lead to better intrinsic recovery from hemiplegia. A detailed study was carried out of recovery of arm function after acute stroke, and compares orthodox physiotherapy with an enhanced therapy regime which increased the amount of treatment as well as using behavioural methods to encourage motor learning. In a single-blind randomised trial, 132 consecutive stroke patients were assigned to orthodox or enhanced therapy groups. At six months after stroke the enhanced therapy group showed a small but statistically significant advantage in recovery of strength, range and speed of movement. This effect seemed concentrated amongst those who had a milder initial impairment. More work is needed to discover the reasons for this improved recovery, and whether further development of this therapeutic approach might offer clinically significant gains for some patients.